Thinking and Reasoning : A Very Short Introduction - Evans, Jonathan St. B. T., 1948- (Great Clarendon Oxford University Press, 2017)
"Our extraordinary capacity to reason and solve problems sets us aside from other animals, but our evolved thinking processes also leave us susceptible to bias and error. The study of thinking and reasoning goes back to Aristotle, and was one of the first topics to be studied when psychology separated from philosophy. In this Very Short Introduction Jonathan Evans explores cognitive psychological approaches to understanding the nature of thinking and reasoning, problem solving, and decision making. He shows how our problem solving capabilities are hugely dependent on also having the imagination to ask the right questions, and the ability to see things from a completely new perspective. Beginning by considering the approaches of the behaviorists and the Gestalt psychologists, he moves on to modern explorations of thinking, including hypothetical thinking, conditionals, deduction, rationality, and intuition. Covering the role of past learning, IQ, and cognitive biases, Evans also discusses the idea that there may be two different ways of thinking, arising from our evolutionary history."--Publisher information.
Include Illustrations and Index
Keywords: Thought and thinking -- Reasoning (Psychology)